FAKTORFAKTOR ANTROPOMETRI YANG BERPENGARUH TERHADAP FUNGSI KOGNITIF DENGAN PEMERIKSAAN MMSE DAN SUBTES MMSE PADA ANAK USIA 1012 TAHUN - Serly, Siti Aminah, Uni Gamayani, Kusnandi Rusmil (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION CHILD DEVELOPMENT IS ALL THE CHANGES THAT OCCUR IN CHILDREN INCLUDING MOTOR COGNITIVE EMOTIONAL AND PSYCHOSOCIAL DEVELOPMENT WHICH BECAME THE BASIS FOR THE NEXT DEVELOPMENTS INTELLIGENCE OF A CHILD IS DETERMINED BY GENETIC FACTORS ENVIRONMENTAL FACTORS SUCH AS STIMULATION AND ALSO THE NUTRITION CHILDREN WITH MALNUTRITION WILL OCCUR TISSUE DAMAGE GROWTH RETARDATION AND IMPAIRED BRAIN DEVELOPMENT ESPECIALLY THE FRONTAL CORTEX THE MINI MENTAL STATE EXAMINATION MMSE CAN BE USED TO MEASURE CHILD COGNITIVE FUNCTION WHILE MEASURING NUTRITIONAL STATUS USING ANTHROPOMETRY